Laser ablation of silicon with THz bursts of femtosecond pulses - Gaudiuso, Caterina; Terekhin, Pavel N.; Volpe, Annalisa; Nolte, Stefan; Rethfeld, Baerbel; Ancona, Antonio (Scientific Reports, 2021)
In this work, we performed an experimental investigation supported by a theoretical analysis, to improve knowledge on the laser ablation of silicon with THz bursts of femtosecond laser pulses. Laser ablated craters have been created using 200 fs pulses at a wavelength of 1030 nm on silicon samples systematically varying the burst features and comparing to the normal pulse mode (NPM). Using bursts in general allowed reducing the thermal load to the material, however, at the expense of the ablation rate. The higher the number of pulses in the bursts and the lower the intra-burst frequency, the lower is the specific ablation rate. However, bursts at 2 THz led to a higher specific ablation rate compared to NPM, in a narrow window of parameters. Theoretical investigations based on the numerical solution of the density-dependent two temperature model revealed that lower lattice temperatures are reached with more pulses and lower intra-burst frequencies, thus supporting the experimental evidence of the lower thermal load in burst mode (BM). This is ascribed to the weaker transient drop of reflectivity, which suggests that with bursts less energy is transferred from the laser to the material. This also explains the trends of the specific ablation rates. Moreover, we found that two-photon absorption plays a fundamental role during BM processing in the THz frequency range.
CRIS-Team Scopus Importer:2023-04-20